Cerebral folate transport deficiency and epilepsy in paediatric patients - Kirik, S.; Akgun, A.; Kok, S. (Wiley, 2024)
[Abstract Not Available]
15th European Epilepsy Congress -- SEP 07-11, 2024 -- Rome, ITALY